Genetic parameters in intra-gene and inter-gene pool crosses of common bean (Phaseolus vulgaris L.) for root distribution - de Melo, Rita Carolina; Grigolo, Sibila; Cerutti, Paulo Henrique; da Costa Lara Fioreze, Ana Carolina; Guidolin, Altamir Frederico; Meirelles Coimbra, Jefferson Luís (Revista Ceres, 2024)
The knowledge about the genetic behavior of roots can be the solution to the main climatic problems and the key for increased production of agricultural crops. In inheritance studies, breeders usually conduct crosses between contrasting individuals to obtain a significant fraction of the genetic variance. To determine genetic parameters in beans from crosses within and between Middle American and Andean gene groups, 64 populations (breeders, F1 and F2) were evaluated under field conditions for the trait root distribution. Crosses between Middle American and Andean gene groups revealed significant estimates for genetic parameters (genetic variance, heritability, and average degree of dominance) compared to intra-pool crosses. However, only 4% of all hybrid combinations evaluated (F1 and F2) showed significant effects when compared to fixed populations (parents). Coupled with the insignificant number of progenies different from the parents, the differences detected revealed inferior performance, compared to the parents. The joining of alleles with identical provenance may be the main cause of the observed effects. The breeding strategy for root distribution should consider more divergent parents.